Is there a link between low parental income and childhood obesity?. (September 2017) - Shackleton, Nichola
The association between familial socioeconomic status and child obesity has created the expectation that low familial income increases the risk of child obesity. Yet, there is very little evidence in the United Kingdom to suggest that this is the case. This article focuses on whether low familial income and family poverty are associated with an increased risk of child obesity. Data from the Millennium Cohort Study (age 7) are analysed. Sequential logistic regression analyses are used to determine whether income has a direct link to childhood weight. The results show no direct relationship between familial income/poverty and weight in childhood. Numerous robustness checks provide considerable evidence that low familial income has no association with children's weight status in the United Kingdom. The results demonstrate that social inequalities in child weight are not driven by differences in income.